Pengaruh Kepuasan Penumpang terhadap Kualitas Pelayanan Maskapai Garuda Indonesia di Bandar Udara Internasional Juanda - Silviyanisyah Silviyanisyah; Febriansyah Ignas Pradana (LPPM Institut Nasional Laa Roiba Bogor, 2022)
During the COVID-19 pandemic period the airport must always be sterile to prevent the spread of the virus. Every passenger must expect a clean airport and comply with existing protocols in the area, region and country to be addressed. A clean airport provides a sense of comfort for passengers. Garuda airlines must still provide good service so that passengers can feel the service provided to the maximum and produce satisfaction for the passengers themselves. This research aims to analyze passenger satisfaction with the quality of Garuda Indonesia airline service at Juanda International Airport and to find out the attributes of service quality that Garuda Indonesia can develop at Juanda International Airport. Surabaya. The study used quantitative methods, with Garuda Indonesia passengers at Juanda International Airport as the subject of the study. The number of research as many as 100 respondents was determined by the formula slovin. From the research that has been done, the following results are obtained: 1) With the calculation of servqual where there are 22 indicators of service quality, where there are only 4 indicators with negative gap values, which means the quality on the service indicator is not in accordance with what the customer expects, while for 18 indicators with positive gap values have been in accordance with what customers expect or expect. 2) Based on the results of the Importance Performance Analysis (IPA) method, the attributes whose service quality can be developed by Garuda Indonesia are attributes that are in quadrant A, because the attributes on quadrant A are considered very important by customers but the quality of service provided is not appropriate. Keywords: Quality of Service, Passenger Satisfaction, Garuda Indonesia, Juanda International Airport